Relevance of Article 31 of the 1945 Indonesia Constitution and Law no. 8 of 2016 in the Perspective of the Theory of Dignified Justice - Wartoyo, Franciscus Xaverius (Faculty of Law, Universitas Pekalongan, 2024)
The government provides education for every citizen and community, including persons with disabilities. From the data in the field, it was found that very few schools and tertiary institutions have infrastructure facilities for persons with disabilities. The main point of discussion in this study is that higher education in services for disability facilities has not been optimally provided in educational environments evenly, only available in a number of state universities, while the private sector has not been many and able to provide infrastructure facilities for disabilities. The method used in this research is the sui generis method in legal research which is called the normative legal method. The 1945 Constitution of the Republic of Indonesia, especially those that regulate disability, namely Law number 8 of 2016, in implementation it is not yet relevant according to the contents in the preamble to the 1945 Constitution of the Republic of Indonesia and has not been realized optimally according to article 31, especially in several private tertiary institutions not yet available service facilities for persons with disabilities overall. It would be nice for the tertiary level, especially private universities, to provide support for people with disabilities with the support of the government, in the teaching and learning process to provide facilities, for example according to the competence of study programs or those with disabilities who are most interested. This research material in accordance with the philosophy of Pancasila and dignified justice